Jajar Legowo Rice Farming Business in South Sumatera Province - Waluyo Waluyo; Suparwoto Suparwoto (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
The aims of this research was to determine the various ways of planting Jajar Legowo in order to increase farmers' productivity and income in irrigated rice fields. The research was conducted in East OKU Regency, starting from April to August 2015. This research disseminated 2: 1; 3:1;, 4:1; Jajar Legowo planting methods and Jajar Tegel (farmer pattern). The data collected included production facilities, labor, and production. The data were obtained from interviews with farmer cooperators who were guided by a list of questions. Secondary data consisted of land area, production and productivity. The data was analyzed by revenue and income analysis, analysis of costs revenue balance (R/C). The farming business was said to be feasible if R/C> 1, followed by analysis of the break-even point of price (TIH) and the breakeven point of production (TIP). The results showed that the 2:1 Jajar Legowo planting method increased productivity by 1.6 t/ha (23.18%) and farmer income of Rp. 5,755,000 (31.67%) compared to the Jajar Tegel method that commonly used by farmers. The financial benefits from applying the Jajar Legowo planting method 2:1, 3:1, and 4:1 were Rp. 23,925,000; Rp. 21,455,000; and 20,755,000, - better than Jajar Tegel method of Rp. 18,170,000. Economically, Jajar Legowo planting method 2:1 was profitable with more profit of Rp 5.590.000 per ha with RC ratio value of 4,18 so that planting method feasible to be developed on a large scale.